A Component Based 3D Collision Avoidance System - Wu, Peng (My University, 2003)
The Coordinate Measuring Machine (CMM) is a key improving the reliability and quality of production. During operation, however, collision between the CMM, probe system, and parts may result in costly damage. Avoiding potential collisions is always an important issue for CMM inspection. This thesis reports design and implementation of an online collision detection system for CMMs. Compared to previous offline collision detection implementations, the new online collision detection system can react to potential collision situations in real time. The collision avoidance system architecture and algorithms are described in this thesis. Each possible CMM translation and probe rotation case is considered. Every component in this system is connected by certain communication protocol and distributed on different computers according to the requirements of applications. This design brings more flexibility to this system. The system components for inspection path planning, collision detection, and CMM motion control are distributed to separate computers, with a TCP/IP based protocol used for communication. This modular, component based design provides more flexibility.
Keywords: 3D collision avoidance; collision avoidance